2019
DOI: 10.1088/1748-9326/aaf431
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of urban heat islands and heat waves under current and future climate conditions and their mitigation using green and cool roofs in New York City and Phoenix, Arizona

Abstract: Urban environments and heat waves interact synergistically and aggravate the thermal environment through the urban heat island (UHI) effect. Of concern is the potential for a projected warmer future climate to further compound heat waves in urban environments. The present study investigates the interaction of a 2006 heat wave in North America with two urban environments (Phoenix and New York City (NYC)) in current climate and future climate simulations. The future climate conditions were generated using the ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 50 publications
3
34
0
1
Order By: Relevance
“…The effect of climate change will be experienced to a greater extent in cities compared with the surrounding rural areas given expected increases in temperature and the vulnerability of the environment to more extreme weather events. In a recent article, Tewari et al studied the interaction of urban heat island and heat waves under current and future climate conditions and found that urban heat island intensity during heat-wave periods and in a warmer climate gets amplified in two large and growing U.S. metropolitan areas [42]. Specifically, they found that the intensity is increased by 21% in Phoenix, AZ, USA, and 48% in New York City for the 2070-2090 period.…”
Section: Impacts Of a Future Climatementioning
confidence: 99%
“…The effect of climate change will be experienced to a greater extent in cities compared with the surrounding rural areas given expected increases in temperature and the vulnerability of the environment to more extreme weather events. In a recent article, Tewari et al studied the interaction of urban heat island and heat waves under current and future climate conditions and found that urban heat island intensity during heat-wave periods and in a warmer climate gets amplified in two large and growing U.S. metropolitan areas [42]. Specifically, they found that the intensity is increased by 21% in Phoenix, AZ, USA, and 48% in New York City for the 2070-2090 period.…”
Section: Impacts Of a Future Climatementioning
confidence: 99%
“…Although future urban air temperatures have been explored both globally and locally (e.g. Adachi et al 2012, Kusaka et al 2012, Kusaka et al 2016, Hamdi et al 2014, Grossman-Clarke et al 2016, Conlon et al 2016, Krayenhoff et al 2018, Tewari et al 2019, Darmanto et al 2019, Takane et al 2019, Lipson et al 2019, few studies have examined the impact on human heat stress in cities. As global climate model (GCM) simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between urban and rural areas in evaporation and anthropogenic heat release contributes to the enhanced UHI effect during heatwaves compared to normal days. Such a phenomenon is found in a wide range of cities (Li et al 2015, Schatz and Kucharik 2015, Ramamurthy and Bou-Zeid 2017, Tewari et al 2019. Considering that the heat risks in urban areas are closely relevant to background temperature and the UHI intensity (Gabriel and Endlicher 2011), it is necessary to investigate the relationship between temperature and the UHI effect (T-UHI).…”
Section: Introductionmentioning
confidence: 99%